(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the causes and types of droughts, their effects on soil fertility, and how to prevent the negative effects of drought stress on soil fertility. In particular, the importance of efficient land management in increasing agricultural productivity and improving land tenure is emphasized, especially as demand for food increases due to population growth. The article recognizes obvious changes in the natural environment and climate, as well as the annual decrease in water resources in agriculture, which leads to soil and land drought. In the next 5-10 years, drought will have a serious impact on soil fertility in Uzbekistan and around the world, harm the way of life of millions of people, destroy ecosystems, and have a major impact on the productivity and quality of agricultural crops. Of great concern are the expansion of areas affected by drought, decrease in soil fertility, and deterioration of soil properties. Drought is linked to climate change and affects hydrology, meteorology, ecology and society. This article, based on Scopus science, examines the extent to which droughts will intensify and their negative impacts on soil conditions over the next 20 years. This article reviews sources aimed at elucidating the scientific basis for the application and impact of innovative methods for mitigating drought stress and improving soil fertility.